Synthesis, characterization and comparative studies on the photophysical and photochemical properties of metal-free and zinc(II) phthalocyanines with phenyloxyacetic acid functionalities - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
The synthesis and characterization of new peripherally and non-peripherally tetra-substituted metal-free and zinc(II) phthalocyanines with 2-, 3- and 4-phenyloxyacetic acid functionalities are described for the first time in this study. The new compounds have been characterized by elemental analysis, FT-IR, UV-Vis, MALDI-TOF and H-1-NMR spectra. Photodegradation, singlet oxygen and fluorescence quantum yields, and fluorescence lifetimes of these compounds are studied in dimethylformamide (DMF). The influence of the substituent position on the phthalocyanine framework (non-peripherally or peripherally), central metal ion (metal-free or zinc) and the position of the COOH group (2-, 3- or 4-position on the phenyloxyacetic acid) on the spectroscopic, photophysical and photochemical properties have been investigated. Non-peripherally zinc(II) phthalocyanines (1b and 2b) and peripherally zinc(II) phthalocyanine (4b) gave good singlet oxygen quantum yields (phi(Delta)) (0.37, 0.39 and 0.38, respectively) which indicate the potential of the complexes as photosensitizers in applications of PDT. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Phenyloxyacetic acid; Fluorescence; Singlet oxygen; Quantum yields; Photodegradation; OXYGEN QUANTUM YIELDS; PHENYLACETIC ACID; FLUORESCENCE; PHOTOSENSITIZERS; SUBSTITUENTS; DERIVATIVES; BEHAVIOR; ALPHA